1995
DOI: 10.1111/j.1365-2990.1995.tb01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Early unsuspected neuron and axon terminal loss in scra pie‐infected mice revealed by morphometry and immunocytochemistry

Abstract: Neuronal loss is often quoted as an element of the pathology of the transmissible spongiform encephalopathies, but few data are published. To determine whether neuronal loss is a salient feature of murine scrapie, and whether there is a relationship with the other hallmark lesions of scrapie we compared the numbers of neurons, severity of vacuolation, axonal bouton density and distribution of prion protein (PrP) in the dorsal lateral geniculate nucleus (dLGN) following intraocular infection of C57BL/FaBtDk mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 20 publications
3
39
1
Order By: Relevance
“…26,27,28 Electron microscopy revealed the well-described ultrastructural hallmarks of the pathology in prion diseased brain 29 and these were present in all ME7-animals from 12 weeks p.i. onwards.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27,28 Electron microscopy revealed the well-described ultrastructural hallmarks of the pathology in prion diseased brain 29 and these were present in all ME7-animals from 12 weeks p.i. onwards.…”
Section: Resultsmentioning
confidence: 99%
“…The dendritic alterations and loss of hippocampal pyramidal neurons have been documented in prion strains additional to ME7 32 and by different routes of challenge than intracerebral. 26 These Synaptic Degeneration in Prion Disease 1613 AJP October 2009, Vol. 175, No.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have indicated the involvement of an apoptotic process in neuronal cell death (13,15,34). For instance, Giese et al (13) demonstrated apoptosis of neurons in the brain of a mouse with experimental prion disease by using the in situ end-labeling technique.…”
mentioning
confidence: 99%
“…These observations confirm previous studies of synaptic protein expression due to prion infection in vivo. Prion diseases are associated with synaptic disorganization and reduction as seen in brains from both patients with CJD (3, 4) and scrapieinfected mice (7,(53)(54)(55)(56). The degeneration and loss of axon terminals occur early during scrapie infections, and in mice it precedes a dendritic spine loss and neuronal cell death (53,55,56).…”
Section: Discussionmentioning
confidence: 99%
“…The vacuoles that give the spongiform character of the degeneration are mainly located in dendrites, which also show varicosities and loss of spines as revealed in Golgi-impregnated specimen (2). In addition to these dendritic changes, reduced expression of presynaptic marker proteins, such as synaptophysin, synaptic-associated protein of molecular weight 25,000 (SNAP-25), 1 syntaxin 1, synapsin 1, and ␣-and ␤-synuclein, has been reported in both clinical materials (3-6) and animal experimental models (7,8) indicating that presynaptic axon terminals are also affected. The mechanisms behind the presynaptic changes and their potential pathogenetic role in the disease are not known.…”
mentioning
confidence: 99%